Validation of questionnaires for restless legs syndrome in the general population: the Trøndelag Health Study (HUNT). (6th March 2022) - Filosa, James; Omland, Petter Moe; Hagen, Knut; Langsrud, Knut; Brenner, Eiliv; Knutsen, Andreas Jarlalein; Drange, Ole Kristian; Bruvik Gravdahl, Gøril; Stjern, Marit; Engstrøm, Morten; Sand, Trond
Summary: Questionnaires for restless legs syndrome have rarely been validated against face‐to‐face interviews in the general population. We aimed to validate the modified Norwegian, seven‐item Cambridge‐Hopkins restless legs syndrome questionnaire and a single diagnostic question for restless legs syndrome. We also aimed to stratify validity at 65 years of age. Among a random sample of 1, 201 participants from the fourth wave of the Trøndelag Health Study, 232 (19%) agreed to participate, out of whom 221 had complete data for analyses. Participants completed the questionnaires for restless legs syndrome immediately before attending a face‐to‐face interview using the latest diagnostic criteria. We calculated sensitivity, specificity, and Cohen's kappa statistic (κ) of questionnaire‐ versus interview‐based diagnoses. We found acceptable validity of the seven‐item modified Cambridge‐Hopkins diagnostic questionnaire for restless legs syndrome ( κ  = 0.37, 95% confidence interval [CI] 0.23–0.51) and good validity of the single diagnostic question ( κ  = 0.47, 95% CI 0.35–0.58). We also found good validity through the combination of modified Cambridge‐Hopkins diagnostic questionnaire for restless legs syndrome items 2 and 5, while item 1 or 2 alone showed only acceptable validity. The single diagnostic question was significantly more valid among those aged <65 years ( κ  = 0.60 versus κ  = 0.26). Both single‐ and two‐item questionnaire‐based diagnoses overestimated interview‐based restless legs syndrome prevalence. The seven‐item modified Cambridge‐Hopkins diagnostic questionnaire for restless legs syndrome will be useful for epidemiological studies although low sensitivity may cause underestimation of true restless legs syndrome prevalence in the general population, especially among elderly. Brief questionnaire‐based diagnoses of up to three items seem best utilised as an initial screen. Future studies should identify brief and even more valid questionnaire‐based diagnoses for restless legs syndrome in order to estimate prevalence accurately in large epidemiological studies.